Gastrodin Inhibits Virus Infection by Promoting the Production of Type I Interferon - Zhou, Yunlian; Li, Mengyao; Lv, Tingyi; Huang, Meixia; Cheng, Beilei; Zhang, Yuanyuan; Zhu, Jie (Frontiers in Pharmacology, 2021)
Type I interferon (IFN-I) plays a critical role in the antiviral immune response. However, viruses have developed different strategies to suppress the production of IFN-I for its own escape and amplification. Therefore, promoting the production of IFN-I is an effective strategy against virus infection. Gastrodin (GTD), a phenolic glucoside extracted from Gastrodia elata Blume, has been reported to play a protective role in some central nervous system -related diseases and is beneficial for the recovery of diseases by inhibiting inflammation. However, the effect of GTD on virus infection is largely unknown. Here we found GTD treatment increased the survival rate of mice infected with vesicular stomatitis virus (VSV) or herpes simplex virus-1 (HSV-1). The production of IFN-I was increased in GTD-treated mice or macrophages compared to the control group, during virus infection. Furthermore, the activation of interferon regulatory factor 3 (IRF3) was promoted by GTD in macrophages upon VSV and HSV-1 infection. Our results demonstrated that GTD could inhibit the VSV and HSV-1 infection by promoting the production of IFN-I in macrophages and might provide an effective strategy against virus infection.